Circa Oaza . Circa Oasis - Bozic, Tatjana (Factum, 1999)
Duration: 00:20:00 A film about a house in the Croatian coastal town of Rovinj that is inhabited by people coming from five different nationalities all with different histories and political opinions. Using cinema verité Bozic reveals the conflicts that arise and how people from such vastly different backgrounds can learn to coexist and live the same roof.